Collaboration in multi-robot systems - Badran, Marwan A.; Khan, Md. Raisuddin; Toha, Siti Fauziah; Zainal Abidin, Zulkifli (Asian Research Publishing Network (ARPN), 2015)
Multi Robot System (MRS) is one of the most important research areas in the field of Robotics and Artificial Intelligence. The study of Multi Robot Systems may take many aspects; therefore, it is useful to study the Multi Robot Systems from a specific point of view to get a more focused idea. In this paper, we present a review of the recent trends in Multi Robot Systems research by focusing at the collaborative aspect. Furthermore, we address the structure of Multi Robot Systems, their applications and the techniques and algorithms used in the collaborative MRS.